Spot-Bonding and Full-Bonding Techniques for Fiber Reinforced Composite (FRC) and Metallic Retainers - Andrea Scribante; Paola Gandini; Paola Tessera; Pekka K. Vallittu; Lippo Lassila; Maria Francesca Sfondrini (MDPI AG, 2025)
Fiber reinforced Composite (FRC) retainers have been introduced as an aesthetic alternative to conventional metallic splints, but present high rigidity. The purpose of the present investigation was to evaluate bending and fracture loads of FRC splints bonded with conventional full-coverage of the FRC with a composite compared with an experimental bonding technique with a partial (spot-) resin composite cover. Stainless steel rectangular flat, stainless steel round, and FRC retainers were tested at 0.2 and 0.3 mm deflections and at a maximum load. Both at 0.2 and 0.3 mm deflections, the lowest load required to bend the retainer was recorded for spot-bonded stainless steel flat and round wires and for spot-bonded FRCs, and no significant differences were identified among them. Higher force levels were reported for full-bonded metallic flat and round splints and the highest loads were recorded for full-bonded FRCs. At the maximum load, no significant differences were reported among spot- and full-bonded metallic splints and spot-bonded FRCs. The highest loads were reported for full bonded FRCs. The significant decrease in the rigidity of spot-bonded FRC splints if compared with full-bonded retainers suggests further tests in order to propose this technique for clinical use, as they allow physiologic tooth movement, thus presumably reducing the risk of ankylosis.